Nonlinear filtering : concepts and engineering applications - Raol, J. R. (Jitendra R.), 1947; Twala, Bhekisipho; Girija, G. (Gopalrathnam), 1954- (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2017)
Nonlinear Filtering covers linear and nonlinear filtering in a comprehensive manner, with appropriate theoretic and practical development. Aspects of modeling, estimation, recursive filtering, linear filtering, and nonlinear filtering are presented with appropriate and sufficient mathematics. A modeling-control-system approach is used when applicable, and detailed practical applications are presented to elucidate the analysis and filtering concepts. MATLAB routines are included, and examples from a wide range of engineering applications - including aerospace, automated manufacturing, robotics, and advanced control systems - are referenced throughout the text.--Provided by publisher.
part Section I Mathematical Models, Kalman Filtering and H-Infinity Filters -- chapter 1 Dynamic System Models and Basic Concepts -- chapter 2 Filtering and Smoothing -- chapter 3 H8 Filtering -- chapter 4 Adaptive Filtering -- part Section II Factorization and Approximation Filters -- chapter 5 Factorization Filtering -- chapter 6 Approximation Filters for Nonlinear Systems -- chapter 7 Generalized Model Error Estimators for Nonlinear Systems -- part Section III Nonlinear Filtering, Estimation and Implementation Approaches -- chapter 8 Nonlinear Estimation and Filtering -- chapter 9 Nonlinear Filtering Based on Characteristic Functions -- chapter 10 Implementation Aspects of Nonlinear Filters -- chapter 11 Nonlinear Parameter Estimation -- chapter 12 Nonlinear Observers -- part Section IV Appendixes Basic Concepts and Supporting Material -- chapter Section IV Appendixes Basic Concepts and Supporting Material Appendix A: System Theoretic Concepts Controllability, Observability, Identifiability and Estimability.
Includes bibliographical references.
Keywords: Stochastic processes; Filters (Mathematics); Nonlinear theory; Engineering mathematics